Receptor-like kinase SlRLK-like positively regulates sugar accumulation and fruit ripening in tomato - Sun, Jiaqi; Zhang, Xinsheng; Yang, Miaofei; Liu, Xin; Jiang, Jing (Frontiers in Plant Science, 2025)
IntroductionThe ripening process of tomato fruits involves many complex changes. The elucidation of the ripening pathways contributes to the reduction of post-harvest losses and improvement of fruit quality. However, much is unknown about how tomato plants precisely synchronize metabolic regulation and fruit maturation.MethodsVIGS, MY2H, BiFC, GUS fused protein activity assays, western-blot, co-expressing in Nicotiana benthamiana leaves and assays of esculin fluorescence in yeast cells, etc.ResultsIn this study, SlRLK-like, a member of the Catharanthus roseus receptor-like kinase 1-like (CrRLK1L) in tomato, was found to be involved in the regulation of sugar transport, lycopene content, and synthesis of ethylene. The overexpression (OE) or virus-induced gene silencing (VIGS) of SlRLK-like increases or decreases sugar accumulation in tomato fruits, respectively. Meanwhile, overexpressing SlRLK-like causes the acceleration of the ripening process of tomato fruit, which also results in the upregulation of ethylene production and lycopene content. SlRLK-like can interact with SlSWEETs (SlSWEET7a and SlSWEET14) and further alter their sucrose transport ability to modulate sugar accumulation. Furthermore, during tomato fruit ripening, SlRLK-like proteins can also interact with ethylene and lycopene biosynthesis-related proteins (SlACS2, SlSAMS4, and SlPSY1) by controlling their gene expression level and protein abundance to promote the process of lycopene and ethylene production. More importantly, sugar accumulation in fruit can enhance ethylene production, which can also speed up the tomato fruit ripening process.DiscussionAs a result, SlRLK-like acts as a positive regulator of tomato ripening. The study provides novel insights into the molecular regulatory networks of tomato fruit quality and ripening, which can be applied to improve tomato cultivation.